ADVOCACY ROLE MODEL NON-GOVERNMENT ORGANIZATION HANDLING STREET CHILDREN DEALING WITH LAW IN INDONESIA - Maemunah, Maemunah; Sakban, Abdul (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
Street children choose life on the road caused by lack of economic factors, family factors that are not harmonious always fight, children feel stressed so that they have a way to live, and their activities on the streets such as busking, begging, and many other activities. The main objective is to describe advocacy role model non-government organization handling street children dealing with law in Indonesia. The research method used is normative juridical with a descriptive-analytic approach and literature study equipped with primary and secondary data sources. Data collection used observation and analysis of documents. Data analysis uses qualitative analysis methods. This study's results indicate that street children in Indonesia have a variety of character problems, primarily economic, family, social, and legal issues. Therefore, the role of community and government institutions is needed to provide complete protection to realize human rights. The role of NGOs in advocating for street children in dealing with the law maximized. The productivity of legal aid institutions has resulted in various forms of legal assistance to street children involved in criminal acts; besides, aid is also in developing interests and talents of street children. The condition is that government assistance is needed to provide a particular budget for NGOs so that the process of advocating for street children carried out correctly. An evaluation of the role of NGOs in advocating for street children requires an in-depth study of other aspects.